LAS ’MARCAS DE USO’ EN LOS DICCIONARIOS DEL ESPAÑOL - Garriga, Cecilio (Revista de Investigación Lingüística, 1997)
The concept of label is in general use in present-day lexicography, although its meaning has yet to be accurately defined. At times it seems to be equivalent to abbreviation, at others to restriction and at others to censure. The fact is, however, that all lexicographers intuitively agree about what labels are, and dictionaries, throughout the ages, have all used indications which give the user information about the usage of a particular lexical item. One of the features of these indications is their heterogeneity, which, all things considered, is the result of the complexity of the linguistic system itself and the difficulty of reflecting it in dictionaries. Recently, this type of information has become more important because of the attemps to create dictionaries which can help production so it is found more frequently in the more modern lexicographic repertories. Even so, there has been little thought about the foundation and the reality of the usage label. This study uses linguistic theory as a starting point from which to explain the information about usage included in dictionaries, traces the historical evolution of this information in the lexicography of Spanish and discusses the situation in the most important dictionaries nowadays. Since lexicography has traditionally been a discipline which is closely connected to practice, knowledge of how these aspects have been treated will help us to draw conclusions about how to impove information on usage in dictionaries.